Meat Hygiene and Health Hazard Awareness Among Butchers & Meat Retailers in Jammu - Rayees Ahmed Bafanda , Jahangir Ali and S. A. Khandi, (Indian Journal of Extension Education, 2017)
The present study was conducted in Jammu district of Jammu and Kashmir State to analyze the meat associatedhealth hazards' awareness among butchers and meat retailers. Data was collected through a well structured interviewschedule from three slaughterhouse (Ten butchers selected randomly selected per slaughter houses) and thirty meatretailers shops (one meat retailer selected from one shop). It was found that contact with infected person and impropermeat handling was considered as a major risk for transmission of diseases by most of meat handlers. Poor awarenesswas found regarding different zoonotic diseases (except bird flu), which can be transmitted through meat handling.Meat handlers avoided the meat handling work only when suffered with major diseases. They were frequently wrongin judging the condition/diseases in which animals should not be slaughtered. The finding indicates that lapses exitbetween meat handlers' decision and the scientifically correct decision and thus final decision about the fitness ofcarcass and offal's must rest only with the veterinarian.